Pengaruh Kompetensi dan Pelatihan Kerja terhadap Kinerja Pegawai pada Biro Umum dan Pengadaan Kementerian Pertanian Republik Indonesia - Fatikha Turrizkiyah; Taat Kuspriyono; Yunidyawati Azlina (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
In the digital era and global competition, employee performance is a key factor in enhancing the effectiveness of public services. Competence and job training are considered two important factors that can support improvements in employee performance within an institution. This research employs a quantitative approach with an associative method to identify correlations and impacts between variables. Data were collected through a questionnaire distributed to 40 respondents using total sampling technique. Data analysis was conducted using SPSS version 21 through validity tests, reliability tests, multiple linear regression, T - tests, F - tests, and the coefficient of determination. The results showed that competence has a positive and significant effect on employee performance, with a t - value of 2.461 and a significance of 0.19, and job training also has a positive and significant effect on employee performance, with a t - value of 7.006 and a significance of 0.000. Simultaneously, competency and job training together influence employee performance by 60.2% while the remaining 39.8% is influenced by factors not discussed in this research. Job training shows a more dominant influence compared to competency.